2020
DOI: 10.1021/acs.joc.0c01579
|View full text |Cite
|
Sign up to set email alerts
|

Direct Synthesis of N,N-Disubstituted Formamides by Oxidation of Imines Using an HFIP/UHP System

Abstract: The straightforward synthesis of N,N-disubstituted formamides using 1,1,1,3,3,3hexafluoroispropanol (HFIP) and H 2 O 2 combination is described. The unique features of HFIP allowed the utilization of a green oxidant such as H 2 O 2 and the products, arising from an oxidation-rearrangement sequence, were obtained in good to high yields under smooth reaction conditions. INTRODUCTION

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…The same laboratory also used the HFIP/UHP system for the preparation of N , N -dibsubstituted formamides from imines (Scheme ). Initial experiments were unpromising, leading to low conversion, imine hydrolysis, or formation of the isomeric amide product. The use of HFIP as the solvent and switching the peroxide source from aqueous H 2 O 2 to anhydrous UHP subdued these side reactions.…”
Section: Oxidations and Reductionsmentioning
confidence: 99%
“…The same laboratory also used the HFIP/UHP system for the preparation of N , N -dibsubstituted formamides from imines (Scheme ). Initial experiments were unpromising, leading to low conversion, imine hydrolysis, or formation of the isomeric amide product. The use of HFIP as the solvent and switching the peroxide source from aqueous H 2 O 2 to anhydrous UHP subdued these side reactions.…”
Section: Oxidations and Reductionsmentioning
confidence: 99%
“…Tomioka reported that an oxidation of cyclic imines by using sodium chlorite under buffered conditions gave amides in good to excellent yield [10d] . These methods were usually suffered from a low yield and a by‐product formamides, which were fully studied by the groups of Baeza [10e] and Ramsden [10f,g] . In presence of NaCN [11a] or carbene catalysis, [11b] aromatic aldimines could be transformed to amides as a sole product through a benzylic anions or aza ‐Breslow intermediates, which were reported by Cheon [11a] and Huang, [11b] respectively (Scheme 1B).…”
Section: Methodsmentioning
confidence: 99%
“…Citation: Mollà-Guerola, L.; Baeza, A. On the other hand, to continue our studies on the use of fluorinated alcohols as solvents and promoters of chemical transformations [2][3][4][5][6], we used fluoroalkyl alcohols to accomplish the above-mentioned transformation (Scheme 1). This idea arose not only because of the unique chemical and physical properties (such as a high hydrogen bond donor ability, low nucleophilicity, high polarity and ionizing power values and slight Brønsted acidity) of fluorinated alcohols [7][8][9], but also because they have both shown to promote nucleophilic substitution reactions onto the so-called activated alcohols (such as benzylic and allylic alcohols) [10] and activate silicon-based nucleophiles [11].…”
Section: Well Stablished Methodology (Eq A)mentioning
confidence: 99%